The ways of the water : a reconstruction of Huastecan Nahua society through its oral tradition - Hooft, Anuschka van 't (Leiden University Press, 2007)
For Huastecan Nahuas, water is a symbolic reference. This book describes the multiple values attached to water through the practice of tale telling in this society. It analyzes several local tales about water manifestations such as floodings, thunderstorms, and waterlords, and explores what these mean to Huastecan Nahuas in their present socio-cultural context. The author shows how tales about this element represent and discuss current themes like the village's right to exist, social cohesion among villagers, the need to show respect towards nature, and life and death. The book reveals how the.